The McDonald’s logo on the construction of knowledge - Tramm, Elda Vieira; Cunha, Jussara Gomes Araújo (Seven Editora, 2023)
This work describes how it is possible to create a significant learning environment during the study of the polynomial function of the 2nd degree, with the objective of giving meaning to the rules and formulas, memorized, in the study of the graph. It was carried out with students from a public school in Salvador, from the 1st year of high school, created around the construction of the McDonald’s M logo where the student was the author of this construction itself. The material used was elaborated with the purpose of articulating studied concepts, reflections, interpretation and construction of an object that was part of the students’ reality. The resources used were: the McDonald’s M figure (reduced size), geogebra software, computer lab, textbook, factsheet of challenging questions (guiding research) during the use of GeoGebra. After performing the activities, it was possible to verify that when working with an object of the student’s real context, the difficulties in reflecting on the definitions and concepts were overcome, for the most part, and the usefulness of knowledge, recognized. The role of the teacher (making returns) and the forms, record of the guiding thread of the investigation, were determinant for the involvement of the students once they reflected on their knowledge and reconstructed them. The study went further when the students applied the concept of vector (horizontal translation) called by them by movement of the constructive parable of this environment, and neither the teacher nor the student can stop asking and investigating. DOI: https://doi.org/10.56238/methofocusinterv1-031